DNA methylation profiling distinguishes Ewing-like sarcoma with EWSR1-NFATc2 fusion from Ewing sarcoma - Kölsche, Christian; Kriegsmann, Mark; Kommoss, Felix; Stichel, Damian; Pfister, Stefan; Jones, David T. W.; Mechtersheimer, Gunhild; Deimling, Andreas von (Journal of cancer research and clinical oncology, 2019)
PurposeRecent studies revealed divergent gene expression patterns in Ewing sarcoma (EwS) with canonical EWSR1-ETS gene fusions and undifferentiated round cell sarcomas (URCS) with EWSR1 rearrangements fused to the non-ETS gene NFATc2. Thus, the question arises whether the latter tumors really belong to EwS.MethodsWe collected five cases matching the group of URCS with EWSR1-NFATc2 fusion and performed DNA methylation and copy number profiling. Results were compared to methylation data of 30 EwS with various EWSR1-ETS fusions and one EwS with FUS-ERG fusion, 16 URCS with CIC rearrangement and 10 URCS with BCOR alteration and a total of 81 EWSR1-associated soft tissue sarcomas including 7 angiomatoid fibrous histiocytomas, 7 clear cell sarcomas of the soft tissue, 28 desmoplastic small round cell tumors, 10 extraskeletal myxoid chondrosarcomas and 29 myxoid liposarcomas.ResultsUnsupervised hierarchical clustering and t-distributed stochastic neighbor embedding analysis of DNA methylation data revealed a homogeneous methylation cluster for URCS with EWSR1-NFATc2 fusion, which clearly segregated from EwS and the other subtypes. Copy number profiles of EWSR1-NFATc2 cases showed recurrent losses on chromosome 9q and segmental gains on 20q13 and 22q12 involving the EWSR1 and NFATc2 loci, respectively.ConclusionIn summary, URCS with EWSR1-NFATc2 fusion share a distinct DNA methylation signature and carry characteristic copy number alterations, which emphasizes that these sarcomas should be considered separately from EwS.
Gesehen am 04.07.2019